Metodologia ACR aplicada a falha de uma embreagem de direção e freio de um trator de esteiras - SILVEIRA, Lucas Mikaell Vitório da (2022)
In maintenance, the occurrence of failures in processes or equipment can compromise the real gains of an organization, so that, generally, these failures end up impacting their corrective maintenance rates. Therefore, it is necessary to control the recurrence of these failures, and for this, it must then rely on the use of structured analytical methods, such as Root Cause Analysis (RCA). With this perspective, the ACR methodology was applied to a failure of a steering and brake clutch of a track type tractor used in desurfacing activities in a mining organization located in the southeast of the state of Pará. With that, it was possible to identify the corrosive wear of the clutch separator valve and the adhesive wear between the surfaces of the friction discs and separator plates of the brake assembly. In addition, from data obtained during the stages of the analytical process, it was possible to identify, with the aid of tools such as the five-why method and the Ishikawa diagram, the causes that led the component to premature failure, among these, the root cause, being the inadequate storage of the clutch in the period before its installation in the asset, as well as contributing causes such as outdated operating procedure and human execution errors. Thus, to contain the recurrence of the identified failure mode, a plan was then elaborated with corrective actions based on the final scenario obtained with the application of the methodology. These actions, after due performance, were effective in preventing the recurrence of clutch failure, among them are the restructuring of a new location for storage of components under adequate protection conditions, updating the operating procedure for installing the clutch and emphasizing the importance use of this document during maintenance activities. Therefore, this work allowed us to conclude that complex flaws can be stratified through the root cause analysis method in effective steps in the identification, not only of the primary cause of the problem, but also of causes tied to different aspects of a process that may have contributed to the occurrence of the failure.